Prevalensi Kelainan Refraksi pada Anak Sekolah Dasar (SD) dan Sekolah Menengah Pertama (SMP) di Kota Batu - Kukuh Mujiono; Yasmin Yasmin; Sony Agung Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the prevalence of refractive errors in elementary school (SD) and junior high school (SMP) children in Batu City, Malang. A total of 659 children were registered as participants in this screening, with 495 children being successfully examined. From the results of the examination, it was found that 17 children (3.4%) had plano vision or no refractive errors, while 366 children (73.93%) had myopia, 111 children (22.42%) suffered from astigmatism, and 1 child (0 .2%) were identified as having hypermetropia. These findings show the high prevalence of refractive errors, especially myopia, among school children in Batu City. Based on the results of this study, it is recommended that routine eye examinations be carried out in schools to prevent the negative impact of refractive errors on children's learning achievement and quality of life.